Oil in the Arctic - Hoult, David P.; Massachusetts Institute of Technology.; United States. Coast Guard. Office of Research and Development. (Cambridge, Mass. : MIT, 1975)
"Prepared for Dept. of Transportation, U.S. Coast Guard, Office of Research and Development."--Cover. "Final report." "Report no. CG-D-96-75." Includes bibliographical references (p. 45). Mode of access: Internet.